hw3soln_f09 - ME 132 Fall 2009 Solutions to Homework 3 1. (...

Info iconThis preview shows pages 1–4. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ME 132 Fall 2009 Solutions to Homework 3 1. ( 3.3, Problem 3) (a) The time constant will be the same regardless of the input u ( t ). However, for the steady state gain , assume that the input is a constant. As given in the notes, the response of the system to a step input, u ( t ) = u for t 0, is y ( t ) = e at y (0)- b a ( 1- e at ) u. If a < 0, then the steady-state output is y =- b a u. The time constant, , and the steady-state gain, , are given by =- 1 a , =- b a . Rearranging these yields a =- 1 , b = . (b) The response of the system to the given input is shown in Figure 1. The output y ( t ) always exponentially approaches a value of u ( t ) that is, the input multiplied by the steady-state gain. The rate of the exponential convergence is determined by the time constant, . During each period of one time constant, the output gets 63% closer to the steady-state value. (c) The response of the system to the given input is shown in Figure 2. The response is identical in shape to that of the previous system. This is because this system is the same as the previous system with time compressed (sped up) by a factor of 1000. The new time constant is 1000 times smaller than the old time constant, so the system responds 1000 times faster. Additionally, the input signal is the same except 1000 times faster. Therefore, the behaviour of the system is the same, only 1000 faster. 2. ( 3.3, Problem 4) We will solve this problem both of the ways that the statement suggested. (Convolution integral) For the linear, time-invariant system x ( t ) = A [ x ( t )- u ( t )] 1 2 4 6 8 1 0 1 2 1 4 1 6 1 8 2 0 2 2 .5 3 3 .5 4 4 .5 5 5 .5 6 T im e y(t) (b ) S yste m w ith = 1 , = 2 Figure 1: System with = 1, = 2. 0 .0 0 2 0 .0 0 4 0 .0 0 6 0 .0 0 8 0 .0 1 0 .0 1 2 0 .0 1 4 0 .0 1 6 0 .0 1 8 0 .0 2 2 2 .5 3 3 .5 4 4 .5 5 5 .5 6 T im e y(t) (c) S yste m w ith = 0 .0 0 1 , = 2 Figure 2: System with = 0 . 001, = 2. 2 the solution (starting from t = 0 with x (0) = x ) is x ( t ) = e At x + integraldisplay t e A ( t ) (- A ) u ( ) d = e At x- integraldisplay t e A ( t ) Ad = e At x- e At A integraldisplay t e A d = e At x- e At A integraldisplay t e A d = e At x- e At A parenleftbigg- t A e At + 1 A integraldisplay t e A d parenrightbigg = e At x + t + 1 A- 1 A e At = ( x + c ) e At + ( t- c ) (Satisfaction of ODE and initial condition) The initial condition can be verified by plugging in t = 0....
View Full Document

This note was uploaded on 10/20/2010 for the course ME 132 taught by Professor Tomizuka during the Spring '08 term at University of California, Berkeley.

Page1 / 14

hw3soln_f09 - ME 132 Fall 2009 Solutions to Homework 3 1. (...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online